2020
DOI: 10.7120/09627286.29.3.285
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of behavioural methodologies utilised to quantify deviations in piglet behaviour associated with castration

Abstract: Surgical castration is a painful procedure that is routinely performed without pain relief on commercial pig (Sus scrofa domesticus) farms. Previous research has focused on quantifying piglet pain response through behaviours. However, to date, behavioural sampling methodologies used to quantify pain associated with castration have not been validated. Therefore, the objective of this study was to validate scan sampling methodologies (2-min, 3-min, 5-min, 10-min and 15-min intervals) to quantify piglet pain res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Given that no physiological biomarkers for pain have been reliably identified and agreed upon, many experts are choosing to explore behavioral pain assessments. For example, behavioral assessment methodologies were recently evaluated for quantifying behavioral deviations as indicators of pain in castrated piglets [ 71 ]. Moreover, this work uncovered only one method that could be validated amongst several techniques used in previous studies, highlighting the need for proactive validation of pain assessment methodologies [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that no physiological biomarkers for pain have been reliably identified and agreed upon, many experts are choosing to explore behavioral pain assessments. For example, behavioral assessment methodologies were recently evaluated for quantifying behavioral deviations as indicators of pain in castrated piglets [ 71 ]. Moreover, this work uncovered only one method that could be validated amongst several techniques used in previous studies, highlighting the need for proactive validation of pain assessment methodologies [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, behavioral assessment methodologies were recently evaluated for quantifying behavioral deviations as indicators of pain in castrated piglets [ 71 ]. Moreover, this work uncovered only one method that could be validated amongst several techniques used in previous studies, highlighting the need for proactive validation of pain assessment methodologies [ 71 ]. Moving forward, refined and scientifically validated pain assessment methodologies for cattle are needed to facilitate reliable drug efficacy evaluation techniques required for continued progress in pain mitigation research and to obtain U.S. FDA approval of an effective drug for controlling procedural pain.…”
Section: Resultsmentioning
confidence: 99%
“…As different studies have demonstrated, behaviour can be efficiently and accurately estimated using scan sampling for behaviour with a long duration (e.g., resting) [4,6,[8][9][10][11] or time sampling for behaviour with a moderate duration (e.g., feeding and locomotion) [3,8]. However, in other studies on pigs, it was not possible to accurately estimate different behaviour with short duration using scan sampling, such as pain associated behaviour [12] or agonistic or sexual behaviour [9]. Hence, the validity of observations of short-term and irregular behaviour should be investigated in greater detail to approve results of existing studies and to determine optimal observation techniques for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, shortening the interval as far as to accurately estimate biting behaviour (e.g., scan sampling every 5 s) would be less efficient than using continuous sampling. Thus, time sampling or continuous sampling is recommended to observe short behaviour such as biting behaviour in pigs [5,[9][10][11][12], although there is no recommendation regarding the required observation length. The observation time per day is often determined by practical factors and rarely exceeds 2 h per day [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying pain associated with castration has been primarily conducted by evaluating behavioral and physiological responses to the procedure, including changes in cortisol, β-endorphins, vocalizations, and pain-related behavioral endpoints [ 1 , 25 ]. Although there are well over fifty publications that evaluate castration pain in pigs, no studies to date have validated these endpoint measurements used to quantify castration pain [ 1 , 2 , 34 ]. When recommending pharmaceutical intervention for pain, the lack of validated measures, combined with poor-quality evidence demonstrating drug efficacy, has prevented the development of nationally accepted industry guidelines for pain management [ 2 ].…”
Section: Discussionmentioning
confidence: 99%